Relações entre memória procedimental e linguagem em pessoas que gaguejam: um estudo com base no processamento da correferência anafórica em português brasileiro - Correia, Débora Vasconcelos (2014)
This dissertation aims to explain how is the processing of coreference in people who stutter (PWS), reflecting on the possibility of an association between stuttering and the presence of difficulties in procedural memory, from the relationship between Alm's Dual Premotor Model (2005) and Ullman´s Declarative/Procedural Model (2001). It is proposed, then, a hypothesis about the connection between the presence of dysfunctions in procedural memory and the linguistic processing of PQG, which was investigated through the ASRT test (Alternating Serial Reaction Time) of procedural memory and two experiments of self-paced reading to the investigation of the phenomenon of inter and intrasentential coreference. In the ASRT test (experiment 1) performed to measure the degree of implicit learning of the participants, the findings suggested a tendency of the groups (PQC and FF) to behave distinctively. PQG showed a pattern of ascending curve, with a positive Spearman's coefficient for the variable cycle, expressing an increase in time of reaction as it increased the number of cycles (stimuli). Which we interpreted as a possible difficulty in the PQG in implicit learning of motor sequences. And the FF showed a descending curve, confirmed by a negative Spearman's coefficient for the variable cycle. Demonstrating that the procedural learning for this group occurred quickly, i.e., the reaction time of the FF reduced as there was an increase in the number of cycles. With these indications that PQG present difficulties in procedural memory, which could interfere in the processing of grammatical aspects according to our hypothesis, we set out to the investigation of the linguistic processing. In experiment 2, the intersentential coreference, performed with the aim at investigating the processing of lexical pronoun (PR) and the repeated name (NR) in the object position between FF and PQC, the results showed that there is no difference in this type of processing between FF and PQC, since both groups showed similar patterns in the average reading time of the critical segment. However, there were a significant effect for the variable tipo de retomada, showing that PR are processed faster than the NR, as previously found by Leitão (2005). Thus, in order to investigate how was grammar functioning in PQG and to attest the hypothesis defended in this dissertation, we set out to the analysis of the phenomenon of coreference in the intrassentential level, in order to isolate the grammatical aspect and eliminate possible interference from the pragmatic and contextual factors. The results pointed to the absence of main effect for the variable group, however, we found a marginally significant interaction effect between the variables group and type of sentence. This interaction can be explained by the fact that the groups react differently to the conditions, departing from the observation that there is an inverse behavior between them, i.e., to the extent that FF are faster in the grammatical condition and slower in agramatical condition, PQG show the opposite pattern. Which corroborates our hypothesis that PQG would have difficulties in perception of breach of grammatical principle. This possibility, confirmed by the statistical evidence foreseen for our findings with the increase of sample, that it directs our search for rejecting the null hypothesis.